Promoting musculoskeletal system soft tissue regeneration by biomaterial-mediated modulation of macrophage polarization - Jinchun Ye; Chang Xie; Canlong Wang; Jiayun Huang; Zi Yin; Boon Chin Heng; Xiao Chen; Weiliang Shen (Bioactive Materials, 2021)
Musculoskeletal disorders are common in clinical practice. Repairing critical-sized defects in musculoskeletal systems remains a challenge for researchers and surgeons, requiring the application of tissue engineering biomaterials. Successful application depends on the response of the host tissue to the biomaterial and specific healing process of each anatomical structure. The commonly-held view is that biomaterials should be biocompatible to minimize local host immune response. However, a growing number of studies have shown that active modulation of the immune cells, particularly macrophages, via biomaterials is an effective way to control immune response and promote tissue regeneration as well as biomaterial integration. Therefore, we critically review the role of macrophages in the repair of injured musculoskeletal system soft tissues, which have relatively poor regenerative capacities, as well as discuss further enhancement of target tissue regeneration via modulation of macrophage polarization by biomaterial-mediated immunomodulation (biomaterial properties and delivery systems). This active regulation approach rather than passive-evade strategy maximizes the potential of biomaterials to promote musculoskeletal system soft tissue regeneration and provides alternative therapeutic options for repairing critical-sized defects.